INTERNATIONAL EXPERIENCE OF POST-WAR RECONSTRUCTION: FINANCIAL TRIGGERS OF SOCIO-ECONOMIC DEVELOPMENT IN THE CONDITIONS OF DECENTRALIZATION - DUGINETS, Ganna; YATSENKO, Olha; PANCHENKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the article is to study the international experience of post-war reconstruction, which will allow identifying sources and forms of financial support for socio-economic development, taking into account the specifics of decentralization. When developing recovery projects and forecasting specific results, conceptual differences between short-term and long-term approaches to development should be taken into account. In the strategic management of investment projects, the categories of “risk” and “vulnerability”, which were developed without taking into account the threats of military invasion, should be rethought. At the center of strategizing should be an approach based on the criterion of “resilience”, which indicates the ability of the analyzed system after a disturbance (endogenous or exogenous in nature) to acquire the specified/desired characteristics that meet the criteria of “system productivity” and “system strength”. If it does not recover after a shock, the system is at risk of collapse. If the shock, due to its duration or intensity, cannot be absorbed by the system, then the stability of the system can be restored (return to the equilibrium that preceded the disturbance) in the medium and long term. What is important here is the "system robustness" - the system’s ability to maintain productivity during a crisis, as well as the "system’s absorptive capacity" - the ability to return to equilibrium after a shock in the short term. Participatory approaches to managing the financial provision of sustainable development of rural communities contribute to achieving positive results in the implementation of these tasks. They promote the active participation of the population in decision-making, which increases the transparency of activities and accountability of local self-government bodies, allows for better consideration of the real needs and priorities of the community, attracts additional resources and investments, and strengthens trust between residents and the authorities. Participatory approaches involve the involvement of all stakeholders in making management decisions in the financial sphere. European experience proves the high efficiency of the functioning of communities that use participatory management in their activities and shows that it contributes to their long-term economic development, social cohesion and environmental sustainability. Participatory management of community financial resources consists in the fact that the population, involved in developing a development strategy for their community, mobilizes more efforts to obtain the desired result. In addition to residents of the relevant community, various types of public organizations, business structures, regional political parties, local leaders, etc. can participate in management. Waste collection should be carried out in accordance with the waste hierarchy and should aim for maximum recycling and reuse using methods and technologies that make circularity efficient and cost-effective. Conversely, approaches that do not promote circularity or create incentives to restrict collection-sorting-recycling practices should be avoided.